Acquired Factor XI Inhibitor Presenting as Spontaneous Bilateral Subdural Hematoma in an Elderly Patient - Vazzana, Natale; Scarti, Luca; Beltrame, Chiara; Picchi, Antonella; Taccetti, Gianni; Fortini, Alberto (Case Reports in Hematology, 2014)
Development of autoantibodies against coagulation factors is an uncommon bleeding disorder associated with cancer, autoimmune conditions, pregnancy, or no apparent disease. Spontaneous FVIII inhibitors are the most frequently encountered; those against FXI have been only anecdotally reported. We report a case of acquired FXI inhibitor presenting as fatal intracranial spontaneous bleeding in an elderly patient with history of cancer and previous transfusions. Few cases of acquired FXI inhibitor have been reported in association with connective tissue disease, cancer, or surgery. Bleeding includes mucocutaneous bleeding, postsurgical hemorrhage, or life-threatening events. Treatment consists of arresting the bleeding and inhibitor eradication. High degree of suspicion is essential to promptly diagnose and treat this uncommon condition.